Exploring Dendrimer Nanoparticles for Chronic Wound Healing - Tetteh-Quarshie, Samuel; Blough, Eric R.; Jones, Cynthia B. (Frontiers in Medical Technology, 2021)
The United States spends billions of dollars to treat chronic wounds each year. Wound healing is complex in nature which involves several intricate multiphase processes that can be delayed for a number of reasons leading to the development of chronic wounds. Wound healing therapies range from topical preparations to surgical repair with treatment options that vary based on other underlying factors like co-infection, age, or co-morbidities such as diabetes. Historically, micelles and liposomes are some of the nanoparticle drug delivery systems explored to treat chronic wounds; however, recent data suggests that dendrimers have shown potential to rival these systems in treating chronic wounds as well as other diseases. This mini review examines advances in dendrimer nanoparticle drug delivery systems to treat chronic wounds.